PARAMYOTONIA CONGENITA & SODIUM CHANNEL MYOTONIA: ARE THEY DISTINCT DISEASES?. Issue 11 (14th October 2015) - Rayan, Dipa Raja; Horga, Alejandro; Matthews, Emma; Sud, Richa; McCall, Samuel; Hanna, Michael
Abstract : Paramyotonia congenita (PMC) and sodium channel myotonia (SCM) have been considered as phenotypically distinct diseases since the potassium aggravated myotonias were first described. They are marked by the presence and absence of weakness and thought to have distinctive neurophysiology patterns. However there is little phenotypic data published comparing large groups of these patients. We investigated a large cohort of 137 patients with mutations in the sodium channel, SCN4A, to identify phenotypic differences between these groups. We found that, whilst there were distinct differences between those patients with Hyperkalaemic periodic paralysis and PMC/SCM, there were no significant phenotypic differences between PMC and SCM patients. This was both when comparing patients with and without episodes of weakness and comparing those with distinct neurophysiology patterns. We therefore propose that PMC and SCM, whilst being separate from Hyperkalaemic periodic paralysis, are part of a spectrum of the same disease and that patients are more likely to lie at a particular point on that spectrum depending on their specific genotype.